Religion as Self-Transcendence. A Simmelian Framework for Authenticity - Montemaggi, Francesca (Simmel Studies, 2017)
Georg Simmel’s writings on religion have too often been overlooked, notwithstanding his undisputed status as one of the founders of sociology. Simmel’s metaphysical inclination may give the impression that his thoughts on religion are closer to theology than sociology. This article proposes an interpretation of Simmel’s notion of religiosity (Die Religiosität) in conjunction with the notion of self-transcendence, part of the philosophy of life (Lebensphilosophie) he espoused towards the end of his life. The article does not pursue a filologically accurate position, but a development drawing on Simmel’s notions. Accordingly, it is proposed to interpret religiosity as a sensitivity to self-transcendence, the awareness of social conditioning, or “facticity”, and the striving towards going beyond it. The tension between facticity and self-transcendence reflects – what Simmel called – the ‘conflict of culture’, the ‘malaise’ of the fragmentation of the self resulting from the social differentiation of modern society. Religiosity, as a sensitivity to self-transcendence, is expressed in the pursuit of authenticity thus countering the conflict of culture. This interpretation allows us to see religion as a path, albeit not the only one, to authenticity, understood as challenging facticity, which echoes in later existentialist philosophy and contemporary empirical studies.